The Palgrave Handbook of Criminology and the Global South (Springer International Publishing, 2018)
The first comprehensive collection of its kind, this handbook addresses the problem of knowledge production in criminology, redressing the global imbalance with an original focus on the Global South. Issues of vital criminological research and policy significance abound in the Global South, with important implications for South/North relations as well as global security and justice. In a world of high speed communication technologies and fluid national borders, empire building has shifted from colonising territories to colonising knowledge. The authors of this volume question whose voices, experiences, and theories are reflected in the discipline, and argue that diversity of discourse is more important now than ever before. Approaching the subject from a range of historical, theoretical, and social perspectives, this collection promotes the Global South not only as a space for the production of knowledge, but crucially, as a source of innovative research and theory on crime and justice. Wide-ranging in scope and authoritative in theory, this study will appeal to scholars, activists, policy-makers, and students from a wide range of social science disciplines from both the Global North and South, including criminal justice, human rights, and penology.